Koperasi dalam Perspektif Sosio-Ekonomi: Karakteristik, Organisasi, dan Manajemen - Dandan Irawan; Rasyid Rahmat (J-Coop : Journal of Co-operative, 2026)
Based on Alfred Hanel's framework, cooperatives are conceptualized as socio-economic organizations that integrate social and economic dimensions. Cooperatives not only focus on commercial profitability but also emphasize social empowerment through economic democracy, where members hold dual roles as owners and users. The organizational structure of cooperatives, comprising the General Assembly, Management, and Supervisory Boards, is analyzed as a fundamental component of cooperative governance. Furthermore, the paper explores internal and external factors affecting cooperative performance, including government regulations, competition, and technological advancements. The application of management functions—encompassing planning, organizing, actuating, and controlling—is evaluated to ensure operational efficiency. The relationship between primary and secondary cooperatives and the role of Apex Cooperatives in enhancing cooperative efficiency and competitiveness are also key areas of discussion. Ultimately, the paper concludes that cooperatives must optimize management practices, leverage technology, and strengthen strategic partnerships to achieve sustainable member welfare.